2017
DOI: 10.1186/s40168-017-0292-4
|View full text |Cite|
|
Sign up to set email alerts
|

Whole metagenome profiles of particulates collected from the International Space Station

Abstract: BackgroundThe built environment of the International Space Station (ISS) is a highly specialized space in terms of both physical characteristics and habitation requirements. It is unique with respect to conditions of microgravity, exposure to space radiation, and increased carbon dioxide concentrations. Additionally, astronauts inhabit a large proportion of this environment. The microbial composition of ISS particulates has been reported; however, its functional genomics, which are pertinent due to potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 81 publications
(89 reference statements)
2
49
1
Order By: Relevance
“…Microbiome monitoring experiments conducted on the ISS were the microbial diversity analyses of the Kibo module [ 32 ], vacuum filter debris [ 33 ], HEPA (High Efficiency Particulate Air) filters [ 34 , 35 ], ISS environmental surfaces [ 36 ], astronaut’s skin mycobiome [ 37 ], and Russian filter debris [ 38 ]. All of these studies were carried out using amplicon-targeted sequencing and were focused on microbial identification only; functional analyses were not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome monitoring experiments conducted on the ISS were the microbial diversity analyses of the Kibo module [ 32 ], vacuum filter debris [ 33 ], HEPA (High Efficiency Particulate Air) filters [ 34 , 35 ], ISS environmental surfaces [ 36 ], astronaut’s skin mycobiome [ 37 ], and Russian filter debris [ 38 ]. All of these studies were carried out using amplicon-targeted sequencing and were focused on microbial identification only; functional analyses were not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one of the major challenges in manned space exploration is protecting astronauts from microbiota dysbiosis. In recent years, with the development of high‐throughput sequencing technology for complex microbial communities, both host‐derived and environmental microbiome have frequently been studied, either in space stations (Checinska et al ., ; Moissleichinger et al ., ; Mora et al ., ; Be et al ., ) or ground‐based space simulations (Li et al ., ; Mayer et al ., ; Sun et al ., ; Blachowicz et al ., ; Schwendner et al ., ; Turroni et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several microbiota monitoring experiments on the ISS have been launched (i.e., NASA's ‘Microbial Observatory’ project (Venkateswaran et al ., ), JAXA's ‘Microbe’ experiment series (Kazuo et al ., ) and ESA's ARBEX/Extremophiles project (Moissleichinger et al ., ). Mora and Checinska (Mora et al ., ; Be et al ., ) found that specific human skin‐associated microorganisms make a substantial contribution to the ISS microbiome, which is not the case in Earth‐based cleanrooms. During the Mars500 project, despite substantial fluctuation with respect to microbial diversity and abundance throughout the experiment, the location within the facility and the confinement duration were identified as factors significantly shaping the microbial diversity and composition, with the crew representing the main source for microbial dispersal (Schwendner et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the collection of nucleic acid may be leveraged to obtain more sophisticated information than is available by PCR and Sanger sequencing. Metagenomics on environmental samples has been well-described in other spheres and is currently being explored for air samples (54)(55)(56)(57).…”
Section: Technicalmentioning
confidence: 99%